Implementation of Systematic Error Correcting Codes for Matching Of Data Encoded (International Journal of Engineering and Computer Science, 2018)
A Computing system is one,where an input data  compared with a  stored data to locate the matching entry.For example translation look  aside buffer  and Cache tag array lookup matching.  In this paper, we  propose  new architecture in order to reduce complexity and latency for matching the data protected with an error-correcting code(ECC).  It is based on  the codeword of an ECC generated by encoding is usually represented in a  systematic form and it consists  the raw data and the parity information. The proposed architecture parallelizes the comparison of the data and that of the parity information.To reduce the latency and complexity, we propose a  new butterfly-formed weight accumulator(BWA)  for The  efficient computation of the Hamming distance.The proposed architecture checks whether the incoming data matches with  the stored data.